Dynamic Changes in Metabolites and Transformation Pathways in Diqing Tibetan Pig Hams During Fermentation Determined by Widely Targeted Metabolomic Analysis - Dan Jia; Siqi Jin; Jin Zhang; Shuyuan Luo; Xinpeng Li; Siew-Young Quek; Xinxing Dong; Dawei Yan (Foods, 2025)
This study investigated the metabolite dynamic changes and transformation pathways in Diqing Tibetan pig (DTP) hams during fermentation (0, 30, 90, 180, 360, 540 d) by widely targeted metabolomics. A total of 873 metabolites in 17 subclasses were detected, with significant changes in 448 metabolites. Additionally, 65 key metabolites were found to be involved in the top 10 pathways, with the top pathways for metabolite markers in mature hams including protein metabolism (2-oxocarboxylic acid metabolism, tryptophan metabolism and amino acid biosynthesis) and lipid metabolism (unsaturated fatty acid biosynthesis and linoleic acid metabolism). Overall, the unique DTP ham taste, flavor, and nutritional value may be contributed to by the significant accumulation of essential amino acids, MSG-like amino acids, free fatty acids (arachidonic acid, docosahexaenoic acid, and eicosapentaenoic acid), citric acid, oxaloacetic acid, succinic acid, and vitamin B. This study facilitates a comprehensive understanding of metabolic profiling and the transformation pathways of DTP hams during fermentation, providing novel insights into the biochemical mechanisms underlying traditional Tibetan pig hams, bridging traditional knowledge with modern omics technologies.